Laparoscopic liver packing to protect surrounding organs during thermal ablation. Issue 5 (October 2014) - Schullian, Peter; Weiss, Helmut; Klaus, Alexander; Widmann, Gerlig; Kranewitter, Christof; Mittermair, Christof; Margreiter, Raimund; Bale, Reto
Abstract Purpose: To evaluate the feasibility of liver packing for the prevention of injury to adjacent organs during thermal ablation of liver tumors. Material and methods: Between January 2005 and March 2010, 47 (52 sessions) patients with non-resectable liver tumors were treated and their tumors (55 primary carcinomas and 65 metastases, 1–12) were isolated from adjacent organs by laparoscopic liver mobilization and packing. Stereotactic radiofrequency ablation (SRFA) comprised body fixation, contrast-enhanced CT, 3-D planning, navigation, needle placement, control CT of needle positions (with image fusion), thermal ablation and control CT (with image fusion). Liver packing was removed laparoscopically thereafter. Complications, primary success and local recurrence rates were analyzed. Results: A total of 120 liver lesions with a median size of 2.4 cm (range 1–15 cm) were treated. Laparoscopic packing could be performed in all patients. The primary success rate of ablation was 91.6% (110/120) and the local recurrence rate was 4.5% (5/110). There was one perioperative death (1.9%). All remaining complications could be managed by radiological interventions. Despite broad surface contact thermal injury of surrounding organs could be prevented in all patients. Conclusion: Liver packing presents a viable and safe option for RFA of tumors with broad surface contact to surrounding organs with excellent local tumor control.